Interaction of berenil with the EcoRI dodecamer d(CGCGAATTCGCG)2 in solution studied by NMR. - Lane, A; Jenkins, T; Brown, T; Neidle, S (1991)
The conformation of the EcoRI dodecamer d(CGCGAATTCGCG)2 has been examined in solution by 1H and 31P NMR. Spin-spin coupling constants and nuclear Overhauser (NOE) enhancement spectroscopy show that all deoxyriboses lie in the south domain, with a small admixture of the north conformation (0-20%). The time dependence of the nuclear Overhauser enhancements also reveals a relatively uniform conformation at the glycosidic bonds (average angle, chi = -114 degrees). The average helical twist is 36.5 degrees (9.8 base pairs per turn). Tilt angles are small (in the range 0 to -10 degrees), and roll angles are poorly determined. Unlike single-crystal X-ray studies of the same sequence, there is no evidence for asymmetry in the structure. Both the NOE intensities and 31P relaxation data imply conformational anomalies at the C3-G4/C9-G10 and the A5-A6/T7-T8 steps. Berenil binds in 1:1 stoichiometry to the dodecamer with high affinity (Kd = 1 microM at 298 K) and causes substantial changes in chemical shifts of the sugar protons of nucleotides Ado 5-Cyt 9 and of the H2 resonances of the two Ado residues. No significant asymmetry appears to be induced in the DNA conformation on binding, and there is no evidence for intercalation, although the binding site is not centrosymmetric. NOEs are observed between the aromatic protons of berenil and the H1' of both Thy 7 and Thy 8, as well as to Ado 5 and Ado 6 H2. These results firmly establish that berenil binds via the minor groove and closely approaches the nucleotides Ado 6, Thy 7, and Thy 8. On the basis of quantitative NOE spectroscopy and measurements of spin-spin coupling constants, changes in the conformations of the nucleotides are found to be small. Using the observed NOEs between the ligand and the DNA together with the derived glycosidic torsion angles, we have built models that satisfy all of the available solution data. The berenil molecule binds at the 5'-AAT (identical to 5'-ATT on the complementary strand) site such that (i) favorable hydrogen bonds are formed between the charged amidinium groups and the N3 atoms of Ado 6 and Ado 18 and (ii) the ligand is closely isohelical with the floor of the minor groove.